A world of many worlds / edited by Marisol de la Cadena and Mario Blaser. - Cadena, Marisol de la; Blaser, Mario, 1966- (Duke University Press, 2018)
Drawing on indigenous social movements and politics, this volume's contributors question Western epistemologies, theorize new forms of knowledge production, and critique the presumed divide between nature and culture-all in service of creating a pluriverse: a cosmos composed of many worlds partially connected through divergent political practices.